FERRONICKEL PRODUCTION TECHNOLOGY FROM LATERITIC NICKEL ORE USING HIGH TEMPERATUR: A CRITICAL REVIEW AND FACTSAGE SIMULATION - Munawaroh, Mona
Nickel is the 24th most abundant element on lithosphere. Nickel is widely used as alloying element and superior commodity because it has strength and high corrosion resistance properties. The world's nickel resources comprise 72% nickel laterite and 28% nickel sulphide. Lateritic nickel ore extraction will produce ferronickel which becomes the raw material of stainless steel. There are many technologies for producing ferronickel such as RK – EF, Direct reduction – Magnetic Separation, and Sintering – Electric furnace. PT Vale Indonesia Tbk. is one of the nickel matte manufacturer that use RK – EF technology, but this technology requires a large energy of 502 kWh/t calcine for the electric furnace, so it becomes a challenge to find alternative technologies that are energy efficient. This literature study aims to review operating parameters on the three technologies mentioned and conduct thermodynamics simulation of laterite nickel ore reduction with Factsage 7.1. The study of literature begins with collecting books, journals, and proceedings related to the lateritic nickel ore reduction process to produce ferronickel or NPI. The literature that has been obtained is then taken for data analysis so that information is obtained as discussion points to answer the objectives of this literature study. The simulation of the nickel ore reduction process is carried out by looking at the effect of temperature on the type of product produced by adding 5% reducing agent. Simulations were also carried out to determine the effect of adding carbon and CaO to the reduced product with an operating temperature of 1550oC. The results of the study show that direct reduction – magnetic separation technology has a lower operating temperature than RK – EF so it is more energy efficient, but the nickel content in the product is lower. Sintering – Electric Furnace technology forms a binder phase in the sinter so that the transportation of intermediate products will be easier compared to calcine in the RK – EF technology. Operating temperature range of RK - EF smelting is 1300-1700oC while the Direct reduction – Magnetic separation is 1100-1300oC. In the Sintering – Electric Furnace process, the best sinter strength is achieved on a raw material basicity of 1.5 and 1.9. The results of the Factsage simulation show that the products of laterite nickel ore reduction with the addition of 5% carbon are Fe-Liquid, slag, olivine, Spinel, and gas phases. The addition of carbon will increase the recovery of Ni and will start to stagnate at the addition of 6% C. The addition of CaO will increase the amount of slag produced and change the slag composition so that the slag produced will have a higher basicity.